Links Between the Psychological Impact of Advertisement Breaking Stereotypes, Self-congruence and Brand Attitude - Lingytė, Laima (Vilnius University Open Series, 2022)
Stereotypes are an integral part of the societal context, encompassing many different social and demographic groups. According to Bordalo et al. (2016), there are three broad approaches to stereotypes, one of which is sociological, most commonly used in the field of marketing research. From a sociological point of view, stereotypes are seen as fundamentally incorrect and degrading generalizations of group characteristics. Accordingly, breaking stereotypes in advertising is a reflection of social change and movements such as feminism and racial equality. It is no secret that advertising, as a sales promotion tool, is playing an increasingly important role in the social context, so the popularity of non-stereotypical advertisement such as 'femvertising' makes it necessary to study the effects of advertisement breaking stereotypes. An empirical study was conducted, to study the links between the psychological impact of advertisement breaking stereotypes, self-congruence and brand attitude.